Animer un cours de FLE à distance: quelle place pour lʼinteraction? - Kutasevych, Halyna; Yakubovska, Nataliya; Smirnova, Maryna (Чернівці–Сучава: БДМУ, 2020)
The relevance of the study is the interaction, determined by the need to focus on one of the significant challenges in distance learning. Recent studies have shown that the effectiveness of distance learning directly relies on the degree of interactivity, which is especially important for learning French. The purpose of the proposed study is to highlight the main aspects of interaction in distance learning of French in synchronous and asynchronous forms. The novelty is that for the first time, the three dimensions of interaction in distance French course are determined: interaction teacher - students, interaction students -students, and interaction students - content. The work used the method of critical analysis of scientific sources and the method of scientific observation of the pedagogical process. Conclusions: Creating interaction in the classroom is essential to student learning and the overall success and effectiveness of distance education. Distance French courses offer interaction among peers, among teacher and students, among students and contentby using different tools in synchronous and asynchronous forms of learning. The use of the latest information and communication technologies ensures the interactive interaction in synchronous and asynchronous forms of education. The rational combination of such technologies with already existing teaching methods is able to become the key to the effective formation of foreign language French-speaking competence among students.
Організація дистанційного вивчення французької мови як іноземної: до питання про місце інтеракції
Keywords: interaction; distance learning; the synchronous form of learning; the asynchronous form of learning